If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(x+6)=-60+2x
We move all terms to the left:
-4(x+6)-(-60+2x)=0
We add all the numbers together, and all the variables
-4(x+6)-(2x-60)=0
We multiply parentheses
-4x-(2x-60)-24=0
We get rid of parentheses
-4x-2x+60-24=0
We add all the numbers together, and all the variables
-6x+36=0
We move all terms containing x to the left, all other terms to the right
-6x=-36
x=-36/-6
x=+6
| -3x+4+6x=23 | | 19x+3+30=180 | | 33=3x-24 | | 7+11x=16x-4x+22 | | 175+7.5=29x | | 5y-2y=1@ | | 2x=5-(9x)/18 | | -2(-8x+3)-5x=3(x-1)-5 | | -3(7x+5)=-8(2x-5) | | 6x-4(1+6x)=-4(x+8) | | (3x2+4)-10=12(4x+16) | | 1/3=m | | 0.5x-12=0.4x | | 2x-2+8x-7+3x-6=180 | | 6h+4=2h | | (-x)/7+1=19 | | 2/3n-6=5n-43 | | -20+5x=7-(-x-5) | | 13v=9v+36 | | 0.5x2+1.5=26 | | 5.4x-5.3=27.1 | | 2x+15+3x-20=0 | | 3(p+2)=3(2p-4)=19 | | 2/3-6=5n-43 | | -5(3x-15)=2(x-29)-37 | | 4(x-10)=2x+40 | | 4=-4+k | | 72=4x+6/2 | | −30+5b= | | 3p+6=6p-12+27 | | -3(1-5x)=-(-3-2x)-6 | | 6+2x=4(-x+9)-60 |